REPRESENTASI PERSONAL INTEGRITY FRONT OFFICE DALAM TUGAS HUMAS UNIVERSITAS NUSA NIPA - MEAK, APOLLONIA WINELCI DUA; BASTIAN, MAYELUS DORI; SEDU, VIKTOR ARIESTYAN (CENDEKIA: Jurnal Ilmu Pengetahuan, 2025)
The task of public relations has an important role in every institution because the task of public relations or public relations is one of the strategies in shaping the image of the institution, whether it is a positive image or a negative image. In forming the image of an institution, public relations usually has extensive relationships, which requires personal integrity. This research aims to find out how front office personal integrity is represented in Nusa Nipa University's public relations duties and find out the obstacles to Nusa Nipa University's front office services. This research uses a qualitative descriptive approach. Data was collected by interviews and observations. The results of this research show that there is a problem found in the front office of the Nusa Nipa University Rectorate, namely that the front office has not received special training regarding personal integrity, apart from that there is only one front office staff, so they experience problems if quite a lot of guests come at the same time. From these problems it can be concluded that the personal integrity of front office staff plays a very important role in creating a positive image of the institution, especially in direct interactions with the public, lecturers, students and guests. ABSTRAKTugas public relations atau humas memiliki peranan penting dalam setiap lembaga karena tugas public relations menjadi salah satu strategi dalam membentuk citra lembaga baik itu citra positif maupun citra negatif. Dalam membentuk citra suatu lembaga, humas biasanya memiliki relasi yang luas untuk itu diperlukan personal integrity. Penelitian ini bertujuan untuk mengetahui bagaimana representasi personal integrity front office dalam tugas humas Universitas Nusa Nipa dan mengetahui hambatan-hambatan pelayanan front office Universitas Nusa Nipa. Penelitian ini menggunakan pendekatan deskriptif kualitatif. Data dikumpulkan dengan wawancara dan observasi. Hasil penelitian ini menunjukan adanya permasalahan yang ditemukan dalam front office Rektorat Universitas Nusa Nipa ialah front office belum mendapatkan pelatihan khusus terkait personal integrity, selain itu staf front office hanya satu orang sehingga mengalami kendala jika tamu yang datang cukup banyak dalam waktu yang bersamaan. Dari permasalahan tersebut dapat disimpulkan bahwa personal integrity staf front office memegang peranan yang sangat penting dalam menciptakan citra positif institusi, khususnya dalam interaksi langsung dengan publik, dosen, mahasiswa dan tamu.